Australia’s Capital Allowance Regimes Between 1915 and 1992: Tax Law Becomes an Instrument of Economic Policy - Allen, Christina (2022)
The depreciation rules for tangible assets in Australian’s income tax law have evolved in two distinct phases. From 1915 to 1992, legislative amendments sought to overcome the limitations of a rigid and limited depreciation system through gradual expansion of the depreciation regime to more and more types of tangible assets and at the same time develop the depreciation rules into a tool for economic intervention. A partial consolidation of the rules in 1992 marked the beginning of a shift in depreciation policy to become a tool in a broader neoliberal agenda. This article explores the evolution of the depreciation rules for tangible assets in the initial seven and a half decades. The history of depreciation rules in this period provides useful insights into the view of Australian governments on both sides of the political divided of tax law as a tool to achieve economic policy objectives.